Investigation of carboxymethyl chitosan in the development of biodegradable soft bait fishing lures - Legault, Ryan; Ahmadi, Ali (Frontiers in Marine Science, 2023)
This paper describes the development and testing of two compositions of biodegradable soft bait fishing lures. A water-soluble form of chitosan, known as carboxymethyl chitosan, was added to the biodegradable lure formula to investigate if the lure properties, such as tensile strength, swelling, and underwater performance, could be improved. A three-month shelf-life study was completed to compare the lure properties of two compositions of biodegradable baits: the first composition containing no carboxymethyl chitosan and the second composition containing 5 wt.% carboxymethyl chitosan. The baits manufactured with carboxymethyl chitosan showed increased tensile strength and underwater performance compared to the lures manufactured without this ingredient. Also, the lures manufactured with carboxymethyl chitosan showed increased swelling when submerged in fresh water, which is not desired; however, these lures stayed intact longer before beginning to degrade. When submerged in salt water, the lures manufactured with and without carboxymethyl chitosan showed similar characteristics. The following results will assist in completing further formula optimizations to improve other hindering properties of the current biodegradable lures. The development of more environmentally friendly fishing options is needed to preserve the world’s oceans and freshwater systems for the future generation of recreational anglers.